Assessment of a Thick-Oxide Transistor from the 22FDX® Platform for 5G NR sub-6 GHz FEMs - Quang Huy Le; Dang Khoa Huynh; Defu Wang; Thomas Kampfe; Zhixing Zhao; Steffen Lehmann (2019 IEEE 2nd 5G World Forum (5GWF), 2019)
This paper investigates the applicability of a thick-oxide transistor from the 22FDX® for 5G NR sub-6 GHz front-end modules. Characterization and evaluation of the GlobalFoundries's FDSOI n-MOSFET regarding RF front-end figure-of-merits, such as output power, efficiency and linearity are discussed. Load-pull measurements are performed to extract the optimal performance. The test transistor delivers saturation power of +5.0 dBm and more than 65% of PAE while maintaining flat transducer gain of 10.2 ± 0.2 dB across the targeted frequency range for a 1.5 V single-ended class AB operation. Besides, the low PAE roll-off in term of reducing supply voltage and the particular 60% PAE at 10 dB output back-off indicate that the DUTs are well suitable for envelope tracking applications. Additional reliability tests at strong compression levels are conducted from which low performance degradation over time is observed even at 9 dB output compression.